Growth Ratio and Efficiency Ratio for Village Revenue and Expenditure Budget in Nagaleah Village Government, Pematang Karau District, East Barito Regency - Syifa, Muhammad Ikhwanul Asy; Meitiana; Mahrita, Ani (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
This study analyzes the effect of the growth ratio and efficiency ratio on the 2022-2024 APBDes period using quantitative methods with SPSS-based statistical analysis. The results showed that the average growth ratio only reached 6.58%, far below the optimal limit of 40%, while the efficiency ratio reached 113.44%, indicating inefficient financial management. Statistical testing revealed that the growth ratio did not have a significant effect on the APBDes, while the efficiency ratio had a significant effect on the APBDes and both simultaneously had a significant effect on the APBDes. This finding suggests that other factors may play a greater role in determining the effectiveness of village financial management. Therefore, a more comprehensive managerial strategy and a more in-depth policy evaluation are needed to improve the efficiency and sustainability of village finances.